PENGARUH MODEL PEMBELAJARAN TIME TOKEN TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI 094155 RAMBUNG MERAH - Simanjuntak, Melvin; Muktar B. Panjaitan; Arni Dasmita Saragih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Time Token learning model on the science learning outcomes of grade V students at SD Negeri 094155 Rambung Merah. This research is quantitative, using a pre-experimental design with a one-group pretest-posttest design. The population in this study were 25 grade V students at SD Negeri 094155 Rambung Merah. The sample used saturated sampling, consisting of 11 female students and 14 male students. The results of this study showed that the pretest average was 52.64 and the posttest average was 79.12. Data analysis using a faired sample t-test revealed a significance level of 15.05 > 2.064, meaning that t count > t table. Therefore, Ha was accepted and Ho was rejected. It can be concluded that the Time Token learning model has an effect on the science learning outcomes of fifth-grade students at SD Negeri 094155 Rambung Merah.